2008
DOI: 10.1083/jcb.200803150
|View full text |Cite
|
Sign up to set email alerts
|

A neuron-specific cytoplasmic dynein isoform preferentially transports TrkB signaling endosomes

Abstract: Cytoplasmic dynein is the multisubunit motor protein for retrograde movement of diverse cargoes to microtubule minus ends. Here, we investigate the function of dynein variants, defined by different intermediate chain (IC) isoforms, by expressing fluorescent ICs in neuronal cells. Green fluorescent protein (GFP)–IC incorporates into functional dynein complexes that copurify with membranous organelles. In living PC12 cell neurites, GFP–dynein puncta travel in both the anterograde and retrograde directions. In cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
120
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(126 citation statements)
references
References 49 publications
(50 reference statements)
4
120
0
Order By: Relevance
“…Interestingly, Par3 was shown to be associated with the dynein complex via light intermediate chain 2 (LIC2) and contributes to the local regulation of microtubule (MT) dynamics at NIH 3T3 cell-cell contacts and also the proper positioning of the centrosome at the cell centre (Schmoranzer et al, 2009). Cells contain distinct dynein complexes distinguished by different combinations of subunit isoforms and probably make possible specific regulation of dynein motor activity and/or cargo binding (Ha et al, 2008). Here we show that dynein intermediate chain 2 (dynein IC2) interacts in an aPKC-regulated fashion with paxillin, controlling FA disassembly.…”
Section: Introductionmentioning
confidence: 79%
“…Interestingly, Par3 was shown to be associated with the dynein complex via light intermediate chain 2 (LIC2) and contributes to the local regulation of microtubule (MT) dynamics at NIH 3T3 cell-cell contacts and also the proper positioning of the centrosome at the cell centre (Schmoranzer et al, 2009). Cells contain distinct dynein complexes distinguished by different combinations of subunit isoforms and probably make possible specific regulation of dynein motor activity and/or cargo binding (Ha et al, 2008). Here we show that dynein intermediate chain 2 (dynein IC2) interacts in an aPKC-regulated fashion with paxillin, controlling FA disassembly.…”
Section: Introductionmentioning
confidence: 79%
“…They found that dynein complexes containing IC-1B, an isoform of the intermediate chain specifically expressed in the nervous system, selectively bind to and transport neuronal TrkB-signaling endosomes. In contrast, dynein complexes containing the highly related, ubiquitously expressed IC-2C intermediate isoform do not do so (Ha et al 2008). Furthermore, TrkA signaling endosomes are not transported by IC-IB-containing dynein complexes, but bind instead to dynein complexes containing IC-2C.…”
Section: Neuronal Signaling Through Endocytosismentioning
confidence: 89%
“…In fungi and higher eukaryotic cells, dynein and kinesin might bind to the same vesicle or to each other directly, and vesicles along a microtubule often undergo bidirectional movement, which could be achieved by tug-of-war between kinesin and dynein or by other regulatory strategies (Ma and Chisholm, 2002;Ligon et al, 2004;Ha et al, 2008;Muller et al, 2008;Shubeita et al, 2008;Soppina et al, 2009;Ally et al, 2009;Hendricks et al, 2010). Nevertheless, the dynamic microtubule plus-end represents a cargo-loading site not only in fungi but also in higher eukaryotic cells (Vaughan et al, 2002;Lenz et al, 2006;Lomakin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%